Assessment of the functional properties of protein extracted from the brown seaweed Himanthalia elongata (Linnaeus) S. F. Gray. (September 2017) - Garcia-Vaquero, M.; Lopez-Alonso, M.; Hayes, M.
Abstract: A protein extract from the brown seaweed Himanthalia elongata (Linnaeus) S. F. Gray was prepared and its functional properties, colour and amino acid composition were assessed for its potential future use by the food industry. The total content of amino acids was determined as 54.02 ± 0.46 g amino acids/kg dry weight, with high levels of the essential amino acids lysine and methionine. SDS-PAGE showed 5 protein bands with molecular weights of 71.6, 53.7, 43.3, 36.4 and 27.1 kDa. The water holding capacity and oil holding capacity were determined as 10.27 ± 0.09 g H2 O/g and 8.1 ± 0.07 g oil/g respectively. Foaming activity and stability were higher at alkaline pH values. The emulsifying capacity and stability of the extract varied depending on the pH and oil used. These results demonstrate the potential use of Himanthalia elongata protein extract in the food industry. Highlights: A novel protein extract from seaweed was evaluated. The functional properties, amino acid and colour of the extract were evaluated. WHC, OHC, solubility, foaming and emulsifying properties were determined. Tris-Tricine SDS-PAGE showed 5 proteins as main constituents of the extract.